Electroanalysis of neutral precursors in protic ionic liquids and synthesis of high-ionicity ionic liquids - Sean, Goodwin; Daniel, Smith; Joshua, Gibson; Jones, Robert; Walsh, Darren A. (American Chemical Society, 2017)
Protic ionic liquids (PILs) are ionic liquids that are formed by transferring protons from Brønsted acids to Brønsted bases. While they nominally consist entirely of ions, PILs can often behave as though they contain a significant amount of neutral species (either molecules or ion clusters), and there is currently a lot of interest in determining the degree of “ionicity” of PILs. In this contribution, we describe a simple electroanalytical method for detecting and quantifying residual excess acids in a series of ammonium-based PILs (diethylmethylammonium triflate, [dema][TfO], dimethylethylammonium triflate, [dmea][TfO], triethylammonium trifluoroacetate, [tea][TfAc], and dimethylbutylammonium triflate [dmba][TfO]). Ultramicroelectrode voltammetry reveals that some of the accepted methods for synthesising PILs can readily result in the formation of non-stoichiometric PILs containing up to 230 mM excess acid. In addition, vacuum purification of PILs is of limited use in cases where non-stoichiometric PILs are formed. While excess bases can be readily removed from PILs, even under ambient conditions, excess acids cannot, even under high vacuum. The effects of excess acid on the electrocatalytic oxygen reduction reaction (ORR) in PILs have been studied, and the onset potential of the ORR in [dema][TfO] increases by 0.8 V upon addition of excess acid to PIL. Based on the results of our analyses, we provide some recommendations for the synthesis of highly-ionic PILs.